In Silico and In Vivo Evaluation of a New Derivative from Memantine and Sinapic Acid (N-Sinapoyl-memantine) as a Candidate for the Management of Alzheimer’s Disease - Andrey Popatanasov; Lyubka Tancheva; Reni Kalfin; Maya Chochkova (Crystals, 2025)
Alzheimer’s disease (AD) is the most common neurodegenerative disease which has a rather complex pathophysiology. During its course, several neurotransmitter neuronal systems get affected such as acetylcholinergic, glutamatergic, gamma-aminobutyric acid (GABA)ergic systems, etc. Such complex physiology requires a sophisticated approach to pharmaceutical management. Therefore, multi-target drugs seem to be an appealing solution. In the present study, we designed and synthesized a hybrid molecule—N-sinapoylamide of memantine, whose parent molecules memantine (MEM) and sinapic acid have been shown in vivo to impact glutamatergic, acetylcholinergic, and GABA-ergic systems, respectively. In silico comparative testing of these molecules was performed, their patterns of interaction with the target enzymes or molecular complexes were analyzed, and some of the mechanisms of action were proposed. Consequently, in vivo testing was performed on a scopolamine mice model of AD and the results overly confirm part of the in silico findings. Therefore, the hybrid molecule (N-Sinapoyl-memantine) seems to be a potent candidate for further evaluation in the management of AD.